A professional agenda: An initial step toward enhancing the quality of teaching in University Malaysia Sarawak. - Lee, Julia Ai Cheng; Lee, Rosy (2002)
This paper was originally written as a proposal to the management of the Faculty of Cognitive Sciences and Human Development, Universiti Malaysia Sarawak (UNIMAS) in the bid to enhance the quality of teaching on a university-wide basis. The recent quality assurance movement on teaching in UNIMAS is an important step to foster excellence in teaching and to eventually meet one of Malaysia’s visions of being a center for quality education by year 2020. Although teaching is one of the core businesses in institutions of higher learning, it is ironic that academics in many universities are not required to possess preparatory training in teaching, unlike schoolteachers. As a forwardlooking university, one of the initial mechanisms suggested in this paper is to conduct a workshop series to all UNIMAS academics. The workshop series comprise topics such as Introduction to University Teaching, How Humans Learn? Assessment, Instructional Design, Instructional Technology, and Learning from the Teaching Practice. The aims of the workshop series are to train the UNIMAS academics in teaching on a short-term basis, to initiate a long-term commitment toward excellence in teaching, and to develop a collaborative academic community that places special commitment to excellence in teaching. The required institutional commitment, the success factors, and the long-term plans for enhancing teaching at UNIMAS are also discussed in this paper.